Key factors in sales management applied to gastronomic establishments - Díaz Duque, Pablo; Salazar Duque, Diego; Vernaza Jarrín, Diana (mktDESCUBRE; Vol 1 No 14 (2019): Fourteenth Edition (July - December)DO - 10.36779/mktdescubre/v#.#, 2019)
The same as with any company, gastronomic establishments must generate sufficient income to cover their costs and also obtain a reasonable profit for the investor that allows them to continue managing the establishment. To reach the level of expected income, it is very important to know what are the factors that affect sales so that the decisions taken are appropriate and generate the necessary income that will allow the economic sustainability of the business. The present study, of qualitative nature and deductive method, raises bibliographic information on the various factors or aspects that influence the sales process; which are key criteria during the management process. As a result of this research, a list of activities that are inherent to the success and fulfillment of business objectives is contemplated, which, identified, treated and applied, according to the stage or process of sale, will allow obtaining better economic returns.